An Investigation of Coding Education Practices in terms of Primary School Students' Algorithmic Thinking Skills and Students' Opinions - Anil Erkan; Sumeyra Akkaya (Journal of Education in Science, Environment and Health)
This study aims to examine the views of fourth-grade primary school students on coding education given through the Scratch program by determining the students' skills in using the program and algorithmic thinking skills. The study was conducted as a one-group study with an embedded mixed design. The study group consisted of 32 students attending the 4th grade in a primary school. The data were collected using the Algorithmic Thinking Skills Scale developed by the researcher, Semi-structured Interview Form, Student Diaries, Scratch Programming Skills Checklists and Researcher Diary. According to the quantitative results of the study, a significant difference was found between the Algorithmic Thinking Skill Scale pre-test and post-test results of the students in the experimental group. According to the results obtained from the Scratch checklists among the qualitative results of the study, it was observed that the students in the experimental group generally added the decor, characters and codes in the projects correctly. According to the student diaries among the qualitative results of the study, it was determined that students generally found the coding course and the projects done in the course enjoyable. The data obtained from the researcher's diaries also supported the student diaries. Finally, according to the student opinions among the qualitative results of the study, it was concluded that the students liked the Scratch program enjoyed making projects and did not get bored. In this context, it is recommended to provide coding education to primary school students and to teach the Scratch program to primary school students.